Software test program: a software residency experience - Sampaio, Augusto; Albuquerque, Carlos; Vasconcelos, Joåo; Cruz, Luckerson; Figueiredo, Luis; Cavalcante, Sergio (Proceedings of the 27th international conference on Software engineering, 2005)
The Software Test Program (STP) is a cooperation between Motorola and the Center for Informatics of the Federal University of Pernambuco. It has been conceived with inspiration on the Medical Residency, adjusted to the software development practice. A Software Residency includes the formal teaching of the relevant concepts and deep practice, with specialization on some specific subject; here the focus is on software testing. The STP has been of great benefit to all parties involved.